2021
DOI: 10.1186/s42483-021-00089-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and simple detection of Phytophthora cactorum in strawberry using a coupled recombinase polymerase amplification–lateral flow strip assay

Abstract: Phytophthora cactorum is a devastating pathogen that infects a wide range of plants and causes Phytophthora rot disease, which has resulted in great economic losses in crop production. Therefore, the rapid and practicable detection of P. cactorum is important for disease monitoring and forecasting. In this study, we developed a lateral flow recombinase polymerase amplification (LF-RPA) assay for the sensitive visual detection of P. cactorum. Specific primers for P. cactorum were designed based on the ras-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…faecium and vanA and vanB genes) were 37 °C for 20 min. Several investigations have shown that the RPA-LF can function well at temperatures ranging from 25–45 °C ( Lu et al, 2021 ; Peng et al, 2019 ) and the faint band was visible in 5 min ( Du et al, 2018a ; Peng et al, 2019 ; Srisrattakarn et al, 2020 ; Wu et al, 2020 ). Similarly, our study found that the RPA worked effectively at a wide temperature range (25–42 °C) and incubation times of 5-30 min could generate a visual signal on the test lines.…”
Section: Discussionmentioning
confidence: 99%
“…faecium and vanA and vanB genes) were 37 °C for 20 min. Several investigations have shown that the RPA-LF can function well at temperatures ranging from 25–45 °C ( Lu et al, 2021 ; Peng et al, 2019 ) and the faint band was visible in 5 min ( Du et al, 2018a ; Peng et al, 2019 ; Srisrattakarn et al, 2020 ; Wu et al, 2020 ). Similarly, our study found that the RPA worked effectively at a wide temperature range (25–42 °C) and incubation times of 5-30 min could generate a visual signal on the test lines.…”
Section: Discussionmentioning
confidence: 99%
“…First, all these tests were performed with the following commercial RPA kits: TwistDx nfo [27,84,[208][209][210][211], TwistDx Basic [212][213][214][215], TwistDx Exo [51], and Amplifier (Agdia) [27,92,[216][217][218]. The main criterion for the selection of a gene as a target for RPA was maximal specificity for the species of interest.…”
Section: Rpa-based Testsmentioning
confidence: 99%
“…Some tests utilize anti-digoxygenin conjugate with carbon NPs in the test zone [211]. The commercial LFA kits were purchased from Millenia [51,[208][209][210], PCRD nucleic acid detector [84,211,222], BioUSTAR [26], and Agdia [27,92,[216][217][218] or assembled and optimized from different membranes (homemade test strips) [212][213][214]. RPA contains a large amount of DTT that induces aggregation of some GNP conjugates, such as streptavidin-GNP [87].…”
Section: Rpa-based Testsmentioning
confidence: 99%
“…Based on this technology, a new isothermal DNA amplification technique, recombinase polymerase amplification (RPA), has emerged (Piepenburg et al., 2006). Compared with LAMP, RPA has no strict requirements on template integrity, reaction temperature and reaction time, so it has application potential in portable nucleic acid detection (Lu et al., 2021). The establishment of a rapid, economical and simple technology for the detection of F .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with LAMP, RPA has no strict requirements on template integrity, reaction temperature and reaction time, so it has application potential in portable nucleic acid detection (Lu et al, 2021). The establishment of a rapid, economical and simple technology for the detection of F. fujikuroi in rice seeds and in water samples during seed soaking could provide accurate guidance for the prevention and treatment of bakanae disease.…”
mentioning
confidence: 99%